2012
DOI: 10.1371/journal.pgen.1002530
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative, High-Throughput Reverse Genetic Screen Reveals Novel Connections between Pre–mRNA Splicing and 5′ and 3′ End Transcript Determinants

Abstract: Here we present the development and implementation of a genome-wide reverse genetic screen in the budding yeast, Saccharomyces cerevisiae, that couples high-throughput strain growth, robotic RNA isolation and cDNA synthesis, and quantitative PCR to allow for a robust determination of the level of nearly any cellular RNA in the background of 5,500 different mutants. As an initial test of this approach, we sought to identify the full complement of factors that impact pre–mRNA splicing. Increasing lines of eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 57 publications
(69 reference statements)
2
40
0
Order By: Relevance
“…The splicing defects we observe are similar in magnitude to those observed when other histone modifications are perturbed. [27][28][29][30]64 In addition, gene-specific splicing defects in budding yeast have been described previously [12][13][14] and could possibly be a result of features of the gene or intron such as the length of the gene, and/or its transcription frequency. Nevertheless, we do observe a trend of decreased splicing efficiency upon removal of Set2, as compared to the wild-type strain ( Fig.…”
Section: H3k36 Methylation Loss Results In Gene-specific Pre-mrna Splmentioning
confidence: 92%
See 1 more Smart Citation
“…The splicing defects we observe are similar in magnitude to those observed when other histone modifications are perturbed. [27][28][29][30]64 In addition, gene-specific splicing defects in budding yeast have been described previously [12][13][14] and could possibly be a result of features of the gene or intron such as the length of the gene, and/or its transcription frequency. Nevertheless, we do observe a trend of decreased splicing efficiency upon removal of Set2, as compared to the wild-type strain ( Fig.…”
Section: H3k36 Methylation Loss Results In Gene-specific Pre-mrna Splmentioning
confidence: 92%
“…The intron-containing genes we analyzed included DBP2, TEF5, and RPS21B, which have previously been analyzed in studies investigating co-transcriptional splicing. 14,[27][28][29]64 Yeast were grown at the permissive temperature prior to RNA extraction and the splicing mutant snu66D served as a positive control.…”
Section: H3k36 Methylation Loss Results In Gene-specific Pre-mrna Splmentioning
confidence: 99%
“…These studies invoked conditional Slu7 functions based on BrPto-3=ss distances, but global substrates are not known in either species (12). While transcriptome analyses of S. pombe grown under varied conditions have provided extensive information on regulated gene expression (47,52), genome-wide transcript isoform analyses have been used to deduce global splicing substrates for only spprp2 ϩ , the U2AF 59 homolog (34). This study found a range of splicing deficiencies on inactivation of this essential factor and, surprisingly, revealed that features other than the 3= Pyn tract confer efficient splicing of specific introns on spprp2-1 inactivation (34).…”
Section: Discussionmentioning
confidence: 92%
“…The efficiency of meiotic intron removal is either regulated or governed by the actions of splicing factors or RNA modifying enzymes that are inessential for vegetative growth (e.g., Mer1, Nam8, Tgs1, Cbc2) (Engebrecht et al 1991;Spingola and Ares 2000;Munding et al 2010;Qiu et al 2011aQiu et al ,b,c, 2012. In addition, comparative genome-wide profiling of vegetative RNA splicing in wild-type and mutant strains deleted for inessential splicing factors, or in conditional mutants of essential factors after shift to restrictive temperature, has fortified the theme that yeast splicing factors are differentially dedicated to splice particular pre-mRNA "clients" (Pleiss et al 2007;Albulescu et al 2012). …”
mentioning
confidence: 99%